2010
DOI: 10.1007/s10661-010-1736-5
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorating effect of N-acetylcysteine and curcumin on pesticide-induced oxidative DNA damage in human peripheral blood mononuclear cells

Abstract: Endosulfan, malathion, and phosphamidon are widely used pesticides. Subchronic exposure to these contaminants commonly affects the central nervous system, immune, gastrointestinal, renal, and reproductive system. There effects have been attributed to increased oxidative stress. This study was conducted to examine the role of oxidative stress in genotoxicity following pesticide exposure using peripheral blood mononuclear cells (PBMC) in vitro. Further possible attenuation of genotoxicity was studied using N-ace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 27 publications
(41 reference statements)
1
17
0
Order By: Relevance
“…7 days) may impair the metabolic activity of PBMCs by the increase of free radicals thereby altering the oxidative status of the cell. This hypothesis is partially confirmed by others (Lowy et al, 1977;Bagchi and Stohs, 1993;Ahmed et al, 2011) who reported that several pesticides including Lindane ( -HCH) induce an intracellular increase of reactive oxygen species.…”
Section: Pwmsupporting
confidence: 61%
“…7 days) may impair the metabolic activity of PBMCs by the increase of free radicals thereby altering the oxidative status of the cell. This hypothesis is partially confirmed by others (Lowy et al, 1977;Bagchi and Stohs, 1993;Ahmed et al, 2011) who reported that several pesticides including Lindane ( -HCH) induce an intracellular increase of reactive oxygen species.…”
Section: Pwmsupporting
confidence: 61%
“…Some animal researches showed that NAC could prevent postischaemic reperfusion injury in hepatic tissue, CCl4 -induced liver damage and brain intoxication induced by propionic acid (PPA) by reducing DNA damage and oxidative stress [46][47][48]. Moreover recent human studies implied that NAC could attenuate pesticide-induced DNA damage in human peripheral blood mononuclear cells, and age-related increases in genetic damage in human T lymphocytes, in vitro and ex vivo [49,50]. Thus, we hypothesized that NAC may act as an antidote of fluorosis through the same mechanism of reducing oxidative stress and DNA damage.…”
Section: Nac Pretreatment Reduced Fluoride-induced Oxidative Stress Amentioning
confidence: 99%
“…This OCP is one of the most toxic pesticides currently on the market and is responsible for a large number of poisoning-related deaths (Moses and Peter, 2010). In animals, it is toxic to the liver, kidney, nervous system, blood system, immune system and reproductive organs (Hashizume et al, 2010;Karatas et al, 2006;Ahmed et al, 2011;Merhi et al, 2010;Briz et al, 2011;Chan et al, 2006;Choudhary et al, 2003;Aggarwal et al, 2008). Due to the risk of adverse effects on human health, the World Health Organization (WHO) classified endosulfan as a moderately hazardous Class 2 pesticide while the Environmental Protection Agency (EPA) considered it as "highly acutely toxic" (Category I).…”
mentioning
confidence: 99%